Handbook of Antenna Technologies 2016
DOI: 10.1007/978-981-4560-44-3_18
|View full text |Cite
|
Sign up to set email alerts
|

Physical Bounds of Antennas

Abstract: Design of small antennas is challenging because fundamental physics limits the performance. Physical bounds provide basic restrictions on the antenna performance solely expressed in the available antenna design space. These limits offer antenna designers a-priori information about the feasibility of antenna designs and a figure of merit for different designs. Here, an overview of physical bounds on antennas and the development from circumscribing spheres to arbitrary shaped regions and embedded antennas are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 96 publications
1
39
0
Order By: Relevance
“…Directivity higher than a nominal directivity is often referred to as superdirectivity and associated with low efficiency and narrow bandwidth [7]. The trade-off between the Q-factor and directivity was shown in [15] and further investigated in [36], [42], [50]. Superdirectivity is also associated with decreased radiation efficiency or equivalently an increased dissipation factor (22).…”
Section: Superdirectivitymentioning
confidence: 99%
“…Directivity higher than a nominal directivity is often referred to as superdirectivity and associated with low efficiency and narrow bandwidth [7]. The trade-off between the Q-factor and directivity was shown in [15] and further investigated in [36], [42], [50]. Superdirectivity is also associated with decreased radiation efficiency or equivalently an increased dissipation factor (22).…”
Section: Superdirectivitymentioning
confidence: 99%
“…These bounds have been verified by optimizing the same problems in CVX [18], [23] for several of the considered cases confirming that the duality gap is zero for these cases. However, it is also interesting to investigate the radiation modes that contribute to the spectral efficiency in (15). To illustrate both of these results this section is divided into four sub-sections.…”
Section: Resultsmentioning
confidence: 99%
“…In Section III it is shown that the only part of the optimal spectral efficiency problem (8) that is dependent on the geometry considered are the eigenvalues n of the radiation modes. This means that optimizing spectral efficiency with a radiation efficiency constraint has been reduced to solving the generalized eigenvalue problem (16), followed by water filling over the singular values σ n given by (15) or (17). This means that it is possible to evaluate the quality of a geometry, in terms of spectral efficiency, by only studying the eigenvalues n of (15) for normalized radiated power on the left and from (17) for normalized dissipated power on the right.…”
Section: Radiation Modesmentioning
confidence: 99%
See 2 more Smart Citations